Pharmacokinetics of Colistin Following a Single Dose of Intravenous Colistimethate Sodium in Critically Ill Neonates. Issue 11 (November 2016) - Nakwan, Narongsak; Usaha, Siripa; Chokephaibulkit, Kulkanya; Villani, Paola; Regazzi, Mario; Imberti, Roberto
Abstract : In this study, we sought to evaluate the pharmacokinetics of colistin after intravenous administration of colistimethate sodium (CMS) in the critically ill neonates with Gram-negative bacterial infections. A single intravenous dose of CMS [approximately 150, 000 IU/kg, equivalent to 5 mg/kg colistin base activity (CBA)] was administered to 7 critically ill neonates. Mean (±SD) maximum plasma colistin concentration and area under the time-concentration curve from 0 to infinity were 3.0 ± 0.7 µg/mL and 25.3 ± 10.4 µg·h/mL, respectively. Time to maximum concentration, half-life, apparent volume of distribution and clearance were 1.3 ± 0.9 hours, 9.0 ± 6.5 hours, 7.7 ± 9.3 L/kg and 0.6 ± 0.3 L/h/kg, respectively. After a dose regimen of 5 mg/kg CBA every 24 hours, the average concentration expected at steady state is 1.1 ± 0.4 µg/mL. In critically ill neonates, a single intravenous dose of 5 mg CBA/kg (approximately 150, 000 IU/kg of CMS) resulted in suboptimal plasma concentrations of colistin. According to our pharmacokinetics data, the dosage of CMS currently used in critically ill neonates is insufficient.